Study of the Lyapunov Exponents in Heart Rate Variability Signals - Casaleggio, A.; Cerutti, S.; Signorini, M. G. (Methods of Information in Medicine, 1997)
Heart rate variability signals obtained from 24 h recordings are analyzed for normal and pathological subjects. This time series contains information about the autonomic nervous system action regulating the beat-to-beat heart rate. Nonlinear contributions to the long period variability have been assessed by the calculation of the entire spectrum of Lyapunov exponents, after the system trajectory reconstruction, starting from the original variability signal. The positivity of Lyapunov exponent values, obtained from an unknown process, can establish whether the structure generating it shows nonlinear chaotic characteristics. This is what happens for the cardiovascular signals. Moreover, the different values obtained for the Lyapunov exponents operate a classification among the considered pathophysiological cases.
Keywords: Heart Rate Variability; Lyapunov Exponents; Chaos Theory; Nonlinear Dynamics